Adoption of the SAMR Model to Asses ICT Pedagogical Adoption: A Case of Makerere University - Lubega, T. Jude; Mugisha, Annet Kajura; Muyinda, Paul Birevu (International Journal of e-Education, e-Business, e-Management and e-Learning, 2014)
For the past decade, Makerere University seen integration of ICTs as an enhancement tool in its pedagogical processes. The level of enhancement has been slow and not satisfactory considering the low number of staff that pedagogically integrate ICT for teaching and learning. Several studies had indicated in the past how e-learning has been implemented in Makerere University but there was no empirical evidence to explain the slow pedagogical ICT adoption in the University. Lack of such information contributed to the lack of concrete interventions that could be devised to transform pedagogical integration of ICT at Makerere University. Using a mixed research approach, a comparative study was undertaken to find out the actual causes of slow pedagogical integration and at the same time suggest interventions that could improve the situation from using ICT as an enhancement tool but a transformative tool as per the SAMR model. These interventions arising from this study could be utilized by any other institution which has slow adoption of ICT for pedagogical purposes.
Keywords: SAMR model; ICT pedagogical adoption; Makerere University